Variations in the Composition, Antioxidant and Antimicrobial Activities of Cystoseira compressa during Seasonal Growth - Martina Čagalj; Danijela Skroza; María del Carmen Razola-Díaz; Vito Verardo; Daniela Bassi; Roberta Frleta; Ivana Generalić Mekinić; Giulia Tabanelli; Vida Šimat (Marine Drugs, 2022)
The underexplored biodiversity of seaweeds has recently drawn great attention from researchers to find the bioactive compounds that might contribute to the growth of the blue economy. In this study, we aimed to explore the effect of seasonal growth (from May to September) on the in vitro antioxidant (FRAP, DPPH, and ORAC) and antimicrobial effects (MIC and MBC) of Cystoseira compressa collected in the Central Adriatic Sea. Algal compounds were analyzed by UPLC-PDA-ESI-QTOF, and TPC and TTC were determined. Fatty acids, among which oleic acid, palmitoleic acid, and palmitic acid were the dominant compounds in samples. The highest TPC, TTC and FRAP were obtained for June extract, 83.4 ± 4.0 mg GAE/g, 8.8 ± 0.8 mg CE/g and 2.7 ± 0.1 mM TE, respectively. The highest ORAC value of 72.1 ± 1.2 µM TE was obtained for the August samples, and all samples showed extremely high free radical scavenging activity and DPPH inhibition (>80%). The MIC and MBC results showed the best antibacterial activity for the June, July and August samples, when sea temperature was the highest, against Listeria monocytogenes, Staphylococcus aureus, and Salmonella enteritidis. The results show C. compressa as a potential species for the industrial production of nutraceuticals or functional food ingredients.